2019
DOI: 10.1186/s12873-019-0242-5
|View full text |Cite
|
Sign up to set email alerts
|

Trends and barriers of emergency medical service use in Addis Ababa; Ethiopia

Abstract: Background The increasing burdens of trauma and time sensitive non-communicable disease in Addis Ababa necessitate a robust emergency medical care system. The objectives of this study were to assess the proportion of patients who used emergency medical services (EMS) and to quantitatively and qualitatively assess barriers to EMS utilization in Addis Ababa. Methods A cross-sectional quantitative and qualitative study was conducted on patients who visited five selected pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 13 publications
8
42
3
Order By: Relevance
“…This finding broadly supports the results of other studies in this area which confirm that ambulance's arrival under five minutes for RTIs and less than eight minutes for heart patients will cause a significant reduction in mortality and other complications [62][63][64]. However, the results of many studies have shown that response time in many countries, especially in LMICs, is higher than the international standards [65][66][67][68]. This problem can be somewhat eliminated by familiarizing prehospital emergency technicians with suburban and urban routes, using satellite and GIS systems, educating the community to open the path for ambulances, constructing dedicated routes, and using Motorcycles.…”
Section: Discussionsupporting
confidence: 87%
“…This finding broadly supports the results of other studies in this area which confirm that ambulance's arrival under five minutes for RTIs and less than eight minutes for heart patients will cause a significant reduction in mortality and other complications [62][63][64]. However, the results of many studies have shown that response time in many countries, especially in LMICs, is higher than the international standards [65][66][67][68]. This problem can be somewhat eliminated by familiarizing prehospital emergency technicians with suburban and urban routes, using satellite and GIS systems, educating the community to open the path for ambulances, constructing dedicated routes, and using Motorcycles.…”
Section: Discussionsupporting
confidence: 87%
“… 24 30 39 43 Private vehicle evacuation was the most common transport option. 9 10 24 44 For example, in Ethiopia, only 20.3% of the sampled trauma patients arrived in the trauma management facilities through ambulance services, 43 whereas in Kenya, less than 10% accessed ambulances. 43 In South Africa, a country with one of the best prehospital EMS, 48.5% of patients used their own means of transport from the trauma scene to the nearest facility.…”
Section: Resultsmentioning
confidence: 99%
“… 9 10 24 44 For example, in Ethiopia, only 20.3% of the sampled trauma patients arrived in the trauma management facilities through ambulance services, 43 whereas in Kenya, less than 10% accessed ambulances. 43 In South Africa, a country with one of the best prehospital EMS, 48.5% of patients used their own means of transport from the trauma scene to the nearest facility. 39 Another South African study found patients with penetrating injuries to be often transported by non-EMS rather than EMS (p<0.001).…”
Section: Resultsmentioning
confidence: 99%
“…The poor economic conditions, households with a low income as well as no health insurance are an obstacle and limitation to accessing healthcare delivery, causing treatment delays. 11,19,20,26,28 The holistic professional approach to the health of migrant people into mainstream healthcare practices, health policy, and local political policy should lead to promoting equity and quality of healthcare service.…”
Section: Discussionmentioning
confidence: 99%